Need for evidence synthesis for quality control of healthcare decision-making - Sathian, Brijesh; van Teijlingen, Edwin; do Nascimento, Israel Junior Borges; Khatib, Mahalaqua Nazli; Banerjee, Indrajit; Simkhada, Padam; Kabir, Russell; Al Hamad, Hanadi (Nepal Journal of Epidemiology, 2023)
Systematic reviews that are out-of-date delay policymaking, create controversy, and can erode trust in research. To avoid this issue, it is preferable to keep summaries of the study evidence. Living evidence is a synthesis approach that provides up-to-date rigorous research evidence summaries to decision-makers. This strategy is particularly useful in rapidly expanding research domains, uncertain existing evidence, and new research that may impact policy or practice, ensuring that physicians have access to the most recent evidence. Addressing global challenges – ranging from public health crises to climate change or political instability - requires evidence-based judgements. An obsolete, biased, or selective information poses risks of poor decisions and resource misallocation. The relatively nascent practice of living evidence proves invaluable in maintaining continuous interest and team engagement. The concept of living evidence has been particularly relevant during the COVID-19 pandemic due to the rapidly evolving nature of the virus, the urgent need for timely information, and the continuous emergence of new research findings. Although the COVID-19 pandemic accelerated the adoption of evidence systems, researchers and funders of research should rigorously test the living-evidence model across diverse domains to further advance and optimize its methodology.